Isolated Renal Calyceal Urothelial Carcinoma Effectively Treated With PD-1 Inhibitor Alone: A Case Report And Literature Review - Li, Shihao; Zhu, Yi; Xu, Zhijian; Liu, Jianjun; Liu, Hongwei (Frontiers in Oncology, 2022)
The discovery of immune checkpoint inhibitors (ICIs) represents a significant step forward in the battle against malignant tumors. In a number of advanced malignancies, ICIs, such as antibodies to programmed cell death protein-1 inhibitor (PD-1) and its ligand, programmed death-ligand 1 (PD-L1), have shown good therapeutic benefits. A 71-year-old male patient was diagnosed with solitary renal calyceal urothelial cancer. The space-occupying lesion in the upper calyx of the left kidney dramatically decreased after 13 treatments with a PD-1 inhibitor (tislelizumab) alone, and the tumor reached partial remission. This case suggests that a PD-1 inhibitor (tislelizumab) alone may be an effective treatment strategy for solitary renal calyceal urothelial carcinoma.